The shishu ladies of Hilo : Japanese embroidery in Hawai'i - Nunes, Shiho S., 1917-; Nunes-Atabaki, Sara, 1957- (Extraordinary lives., 1999)
Annotation The Shishu Ladies of Hilo traces the teaching of shishu (Japanese embroidery) in Hawai'i and describes in detail the modifications made to traditional motifs and materials. It is, however, much more than a historical record of a textile art form. It raises questions about the relationship between the women who made shishu, their ethnicity, and their needlework -- in short, the role of art in achieving ethnic identity.